Aprovechamiento de la cáscara de limón mandarina (Citrus × limonia) en la extracción de aceite esencial y obtención de harina para su aplicación agroindustrial - Evelyn Jhoana, Farinango Pineida (2024)
The objective of this research was the use of mandarin lemon peel (Citrus limonia) from the Shushufindi Canton - Ecuador in the extraction of essential oil and obtaining a type of non-conventional flour for application in a new agro-industrial product. A physical-chemical and proximal analysis of the raw material was carried out and its essential oil was subsequently extracted using the supercritical fluid method using CO2 as a solvent. To obtain optimal performance in the extraction process, the operating parameters were evaluated by applying the Response Surface Methodology with Box-Behnken design in its three high, medium and low levels, establishing three factors for statistical analysis; Factor A (pressure) 25:35:45 MPa, Factor B (temperature) 50:57.5:65 °C and Factor C (particle size) 0.25: 0.88: 1.5 mm, maximizing performance at 0.89 %. Applying the parameters, Pressure 45 MPa, Temperature 55°C and Particle size 0.55mm, the volatile components present in the extracted essential oil were subsequently analyzed by gas chromatography coupled to mass spectrometry, obtaining 7 high peaks predominating the D-component. Limonene with retention time 6,006 min. Finally, 96% of the residue retained in the extraction vessel was recovered and reprocessed to obtain a type of non-conventional flour, which was analyzed bromatologically and microbiologically, presenting results that are within the quality and food safety requirements. The non-conventional flour was used in the formulation of an aromatic tea which, when applying a sensory analysis, obtained a higher percentage of acceptability for formulation No. 2: Green tea 90% with mandarin lemon peel flour 10%. In conclusion, FSC extraction contributes to maximum use of waste (lemon peel) obtaining quality by-products.